Construction and Selection of an Entomopathogenic Fungal Library From Soil Samples for Controlling Spodoptera litura - Chang, Ju-Chun; Wu, Shin-Shan; Liu, Yao-Chia; Yang, Yu-Hong; Tsai, Yi-Fang; Li, Yi-Hsuan; Tseng, Ching-Tzu; Tang, Li-Cheng; Nai, Yu-Shin (Frontiers in Sustainable Food Systems, 2021)
Chemical pesticides have been used for pest control for many decades, but they cause serious problems, including insecticide resistance, secondary pest resurgence, and negative environmental impacts. Therefore, sustainable alternatives to chemical pesticides are necessary for pest control. Entomopathogenic fungi (EPF) are natural epizootic pathogens of insects, and some of them have been used as microbial biocontrol agents. Herein, we attempted to construct an entomopathogenic fungal library (EFLib) via the “Tenebrio molitor pathogenicity-based fungal collection method (TmPC)” to select EPF for control of the serious agricultural pest Spodoptera litura. A total of 172 soil samples were collected in northern and central Taiwan for EFLib construction. The isolation efficiency of TmPC was 64.02%. The EFLib consisted of 101 isolates and was designated the National Chung Hsing University (NCHU) EFLib. Among these isolates, 26 showed high virulence (mortality= 100%) to T. molitor larvae. Based on the results of molecular identification, the highly virulent isolates belonged to 7 genera, including Beauveria, Clonostachys, Fusarium, Cordyceps, Penicillium, Purpureocillium and Metarhizium. To evaluate the potential of these isolates for Spodoptera litura control, 12 isolates were selected for pathogenicity screening against S. litura larvae. A total of 6 EPF isolates belonging to the genera Beauveria and Metarhizium showed rapid killing of S. litura larvae. To rank the potential of these fungal strains for pest management, the 6 isolates were subjected to thermotolerance and conidial production assays, and a novel effective conidia number (ECN) formula was applied. The results indicated that the ECN index of Beauveria australis (NCHU-113) was much higher than that of Metarhizium isolates. However, among the Metarhizium isolates, NCHU-95 showed the highest ECN index. Altogether, NCHU-69 and NCHU-113 should be further tested in field trials. To our knowledge, this is the first attempt to integrate pathogenicity or virulence and ECN data into EPF screening and ranking, providing a baseline for mass selection of potential EPF strains for further applications.